Dynamic penile peak systolic velocity predicts major adverse cardiovascular events in hypertensive patients with erectile dysfunction. Issue 5 (May 2016) - Ioakeimidis, Nikolaos; Vlachopoulos, Charalambos; Rokkas, Konstantinos; Kratiras, Zisis; Angelis, Athanasios; Samentzas, Alexis; Fassoulakis, Charalambos; Tousoulis, Dimitris
Abstract : Objective: Hypertension is associated with an abnormal penile blood flow. Reduced dynamic penile peak systolic velocity (D-PSV) correlates with adverse cardiovascular outcomes. The aim of this study is to investigate whether abnormal penile blood flow predicts major adverse cardiovascular events (MACE) in hypertensive men. Methods: In total, 298 hypertensive men (55 ± 9 y/o) without known cardiovascular disease or diabetes were evaluated for cavernous vascular disease severity by dynamic penile Doppler ultrasound. The whole population was divided into tertiles according to D-PSV reduction (low tertile <25 cm/s; middle tertile 25–35 cm/s; and high tertile >35 cm/s). Predictive performance was evaluated with calibration, discrimination, and reclassification. Results: During the mean follow-up period of 4.9 years, a total of 22 (7%) MACE occurred. D-PSV level was associated with MACE and the differences between the tertiles were significant (Mantel log-rank test: 6.54; P < 0.01). A Cox proportional hazard model showed that study participants in the lowest D-PSV tertile (<25 cm/s) had an approximately 3.5-fold higher MACE risk compared with those in the highest D-PSV tertile (>35 cm/s) after adjustment for age, systolic pressure, metabolic parameters, smoking, C-reactive protein, and testosterone levels. Low D-PSV did not significantly improve the C-statistic model (0.774 vs. 0.767; P = 0.44), whereas the calibration was satisfactory (Hosmer–Lemeshow X 2 = 8.73, P = 0.30). When only intermediate-risk patients were evaluated, the risk reclassification beyond traditional risk factors resulted in a clinical net reclassification index of 9.2% that was marginally significant ( P = 0.07). The integrated discrimination improvement index showed better performance of the model that included D-PSV compared with the reference model in identifying MACE (improvement index: 0.047, P = 0.038). Conclusion: Low-penile blood flow predicts MACE in hypertensive patients free of clinical atherosclerosis. This predictive ability is independent of the severity of hypertension and decreased testosterone that is often present in such patients.